Usability and acceptability testing of a Plan of Safe Care in a mobile health platform - Isaacs, Krystyna R.; Bajracharya, Elina; Taylor, Shantae; Chang, Katie; Washio, Yukiko; Parker, Trenee; Paul, David A.; Ma, Tony X. (Frontiers in Psychiatry, 2023)
Purpose Women who are pregnant or parenting while recovering from substance use disorder (SUD) are at risk for insufficient recovery support. With the federal mandate, implementation has been left to each state for the Plan of Safe Care (POSC), leading to challenges in providing comprehensive care coordination and meeting federal reporting requirements. Methods This research tests the usability and acceptability of a POSC platform, called SAFE4BOTH, which combines a mobile health (mHealth) app for use by mothers with substance use disorder (MSUD) with a web-based case management system for use by stakeholders to reduce the issue of fragmented postnatal maternal and infant care. The platform was designed to enable access to services, improve reporting task workflow, and assist in improving interactions between mothers and service providers. After applying a user-centered design approach, the usability and acceptability of the SAFE4BOTH platform were evaluated using focus groups, interviews, and a System Usability Scale (SUS). The evaluation involved four staff members from a Medication for Addiction Treatment clinic (comprising of three case management workers and one peer counselor), four state employees of the Delaware Division of Family Services, and 20 mothers with MSUD who had delivered infants in need of a POSC. Features tested in the SAFE4BOTH platform included a secure, web-based POSC, a contingency management-based reward system, a micro-learning library, a resources locator, a chat messaging and videoconferencing system, a directory for contact management, a QR code reader, use of an appointment compliance system engaging geofencing, and an enhanced calendar. Family services and treatment center staff accessed SAFE4BOTH from their laptops or tablets, and MSUD accessed SAFE4BOTH from their phones. Results Family services staff, treatment center staff, and MSUD participants rated SAFE4BOTH as usable and acceptable with average System Usability Scale scores of 68.1 (SD 8.5), 92.5 (SD 11.73), and 78.4 (SD 12.5) (respectively). Conclusion The platform was judged both usable and acceptable by all three target populations (family services staff, treatment center staff, and MSUD). Further studies are planned to explore the efficacy of longitudinally supporting the mother’s recovery and the infant’s healthy development.